Cognitive behavior therapy : basics and beyond - Beck, Judith S. (New York The Guilford press, 2021)
"The leading text for students and practicing therapists who want to learn the fundamentals of cognitive behavior therapy (CBT), this book is eminently practical and authoritative. In a highly accessible, step-by-step style, master clinician Judith S. Beck demonstrates how to engage patients, develop a sound case conceptualization, plan treatment, and structure sessions effectively. Core cognitive, behavioral, and experiential techniques are explicated and strategies are presented for troubleshooting difficulties and preventing relapse. An extended case example and many vignettes and transcripts illustrate CBT in action"--
Includes bibliographical references and index.
Keywords: Cognitive therapy